(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
Experiments about marine fish farming in Syria focused mainly on Flathead grey mullet Mugil cephalus, which is considered as one of the important economic fish and desirable for human consumption. The infection of farmed fish by parasitic crustaceans, especially Copepoda, may cause a great economic losses. the current study aimed to investigate Copepoda at M. cephalus in Syrian marine waters (Lattakia and Jableh ports). Fish samples were collected from July 2020 to July 2021. 238 fish individuals were collected and examined. The parasite Caligus pageti (Caligidae: Copepoda) was isolated from the caudal fin of M. cephalus. The infection was only recorded on October, with an extensity and intensity of infection 2.1% and 1.2 parasites/fish, respectively. This is the first record of this parasitic species on M. cephalus in the Syrian marine waters.